Preserving Visual Functions During Gliomas Resection: Feasibility and Efficacy of a Novel Intraoperative Task for Awake Brain Surgery - Conti Nibali, Marco; Leonetti, Antonella; Puglisi, Guglielmo; Rossi, Marco; Sciortino, Tommaso; Gay, Lorenzo Gabriel; Arcidiacono, Umberto Aldo; Howells, Henrietta; Viganò, Luca; Zito, Paola Cosma; Riva, Marco; Bello, Lorenzo (Frontiers in Oncology, 2020)
Objective The intraoperative identification and preservation of Optic Radiations (OR) during tumor resection requires the patient to be awake. Different tasks are used. However, they do not grant the maintenance of foveal vision during all testing, limiting the ability to constantly monitor the peripheral vision and to inform about the portion of the peripheral field that is encountered. Although hemianopia can be prevented, quadrantopia cannot be properly avoided. To overcome these limitations, we developed an Intra-operative Visual field Task (iVT) to monitor the foveal vision, alerting about the likelihood of injuring the OR during task administration, and to inform about the portion of the peripheral field that is explored. Data on feasibility and efficacy in preventing visual field deficits are reported, comparing the outcome with the standard available task (Double-Picture-Naming-Task,DPNT). Methods Patients with a temporal and/or parietal lobe tumor in close morphological relationship with the OR, or where the resection can involve the OR at any extent, without pre-operative visual-field deficits (Humphrey) were enrolled. 54 patients were submitted to iVT, 38 to DPNT during awake surgery with brain mapping neurophysiological techniques. Feasibility was assessed as ease of administration, training and mapping time, and ability to alert about the loss of foveal vision. Type and location of evoked interferences were registered. Functional outcome was evaluated by manual and Humphrey test; extent of resection was recorded. Tractography was performed in a sample of patients to compare patient anatomy with intraoperative stimulation site(s). Results The test was easy to administer and detected the loss of foveal vision in all cases. Stimulation induced visual-field interferences, detected in all patients, classified as detection or discrimination errors. Detection was mostly observed in temporal tumors, discrimination in temporo-parietal ones. Immediate visual disturbances in DPNT group were registered in 84% vs 24% of iVT group. At 1-month Humphrey evaluation, 26% of iVT vs 63% of DPNT had quadrantopia (32%symptomatic); 10% of DPNT had hemianopia. EOR was similar. Detection errors were induced for stimulation of OR; discrimination also for other visual processing tract (ILF). Conclusion iVT was feasible and sensitive to preserve the functional integrity of the OR.